PENERAPAN MODEL BELAJAR KONSTRUKTIVISME DALAM PEMBELAJARAN MENULIS BAHASA INDONESIA:Studi Eksperimen atas Kemampuan Menulis Bahasa Indonesia pada Siswa Kelas II SMPN I Banjaran Kabupaten Bandung - Nurjanah, Nunuy (2005)
The research was conducted as the needs for improving the students' writing skills in learning writing in Indonesian in secondary schools (SMP). The survey indicated that teaching writing had not optimazed the students' writing skills, but were still dominated by the teachers through lecture and question-answer methods. Generally, the aim of the research is to develop an effective model in learning and teaching writing. Specifically, this research is expected to obtain an illustration of acceptability, comparison, impact, strength, shortcomings, and the results of learning through constructivism learning model in learning writing. This research used a quantitative approach, and a quasi-experimental method. The subjects of this research were the second grade students of SMP N I Banjaran that involved 41 students in the experimental class I, 42 students in the experimental class II, and 42 students in the control class. The instruments of collecting data were tests, field observations, questionaires, and interviews. The statistical procedure for the quantitative method was a t-test, while the descriptive analysis was used for interpreting the qualitative data. It was concluded that (1) the constructivism learning model could generally be accepted by the students as an assistance in learning writing, (2) the constructivism model showed comparatively more successful than the non-constructivism model in control class, (3) the constucvtivism model was generally able to improve all aspects of writing skills, (4) the strength of constructivism learning model was that it could train students' cognitives, motivate students' creativity, and provide a condusive learning environment for utilizing nature as a learning resource, (5) the weakness of this model was that it took a relatively long time of adaptation for self-learning to construct the knowledge, and (6) the constuctivism model provided significant improvement to the students' writing skills of experimental groups. This study may theoritically and practically affect the development of the constructivism learning model. Theoritically, this study recommends that the students should be regarded as individuals with unique potentials for development, not as a rubish bin. Practically, this study also recommends that the constuctivism learning model is required to develop social intelligence of the students to develop their creativity through writing.